Elfriede Jelinek - Rita, Svandrlik (Biblioteca di Studi di Filologia Moderna, 2008)
This volume consists of a collection of essays by five German scholars from various Italian universities - R. Calabrese, R. Caruzzi, M. Fancelli, L. Perrone Capano, R. Svandrlik (editor) - and N. Šlibar from the University of Lubiana, that meld formal research and musical pace and structure with the pitiless radicalism and the consistency of the issues addressed, first and foremost the oppression inherent to power relations. In the commitment to reveal the mechanisms of manipulation, from the most obvious to the most subtle, the author herself becomes a manipulator of language of exceptional creativity and daring, with the guiding thread of the gender perspective. The volume is completed by the translation of the speech made by the Austrian writer when she was awarded the Nobel prize in 2004, and by a bibliography (edited by Claudia Vitale), focused in particular on the reception in Italy and on the scarcity of Italian scientific studies.